Perylene derivative films: Emission from higher singlet excited state - Fernandes, José Diego [UNESP]; Pazin, Wallance Moreira [UNESP]; Macedo, Wagner Costa [UNESP]; Teixeira, Silvio Rainho [UNESP]; Lima, Sergio Antonio Marques [UNESP]; Batagin-Neto, Augusto [UNESP]; Leopoldo Constantino, Carlos José [UNESP] (Elsevier, 2020)
Transitions from the singlet electronic excited states higher than S1 level (S2) to the fundamental state (S0) are unlikely, although such transitions are observed for perylene derivative compounds. This rareness led us to investigate the role of the molecular structure of two perylene derivatives (bis(butylimido) – BuPTCD and bis(phenetylimido) – PhPTCD), as well as their supramolecular arrangements, such as molecular organization, crystallinity, and molecular aggregates (before and after thermal treatment) on the radiative transition S2→S0. The emission spectra of BuPTCD and PhPTCD solutions (monomers) indicated that differences in their molecular structures (lateral groups) do not influence such transitions. Besides, it was verified that the relative intensity (RI) S1→S0 over S2→S0 (RI = IS1→S0/IS2→S0) obtained for BuPTCD and PhPTCD PVD films increases around 15 and 1.5, respectively (in comparison to their respective solutions). However, it was surprising to observe a decrease of RI = IS1→S0/IS2→S0 by a factor of 88 for both BuPTCD and PhPTCD PVD films after their thermal treatment at 200 °C for 2 h. The latter led to an increase of the emission intensity from S2→S0 transition in relation to S1→S0. The decrease of H aggregates, presence of J aggregates and formation of other types of molecular aggregates, induced by thermal treatment, seem to be the cause of the S2→S0 emission increase, which is supported by theoretical calculations.
Keywords: Higher singlet electronic excited state; Internal conversion; Perylene; PVD films; Supramolecular arrangement; Thermal treatment